Assessing Organizational Culture as A Mediator Between Leadership Style and Employee Performance in Public Sector Organizations - I Gusti Ayu Panca Dewi; I Komang Oka Permadi (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The primary purpose of this research is to examine the relationship between approach to management and workforce output; the secondary purpose is to examine the role of corporate culture in moderating this relationship in publicly traded organizations. The present study utilizes a quantitative methodology, employing primary data that was gathered via questionnaires. The population from which the sample of respondents was drawn comprised 208 employees. The Slovin formula was used to determine the sample of 137 respondents. The data analysis was executed using Partial Least Square through SmartPLS 3.2.9. This study suggested that leadership style has a favorable and substantial impact on employee performance and organizational culture. Organizational culture strongly and beneficially impacts employee performance. The style of leadership and workforce performance can be affected by corporate culture, according to the present study. These findings indicate that performance enhancement is influenced by two factors: the effectiveness of leaders in directing and motivating employees, and the organization's ability to establish consistent, adaptive, and supportive values, norms, and work behaviors. These factors contribute to the sustainable achievement of organizational goals. The findings underscore the significance of the interplay between leadership and organizational culture as the crux for enhancing work behavior, task execution effectiveness, and the attainment of institutional objectives in a more efficacious manner.